2012
DOI: 10.1088/0957-0233/23/12/125603
|View full text |Cite
|
Sign up to set email alerts
|

High temperature displacement and strain measurement using a monochromatic light illuminated stereo digital image correlation system

Abstract: This paper describes full-field, three-dimensional, non-contact measurements of displacement and strain under high temperature condition based on digital image correlation (DIC). To conduct DIC measurements at high temperatures, two important factors need to be considered:(1) the ability of the coating to resist heat and withstand deformation without cracking or peeling off; (2) the radiation from the specimen's surface at high temperature. This paper proposes a solution to both of the most important issues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…Motivated by the increasing interest in applications involving significant thermal effects, such as aero-engines, spacecraft re-entry, aircraft hypersonic flight, and nuclear power applications, recent efforts have extended the upper temperature limit of the DIC technique by the use of optical bandpass filters and narrow band lighting, which reduces the influence of light radiated by the specimen at high temperatures [1][2][3][4][5][6]. Grant et al demonstrated this approach for hightemperature DIC by using blue light along with blue range bandpass filters to measure the coefficient of thermal expansion of RR1000 (a nickel-based alloy) at temperatures up to 1000°C with two-dimensional (2D)-DIC [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the increasing interest in applications involving significant thermal effects, such as aero-engines, spacecraft re-entry, aircraft hypersonic flight, and nuclear power applications, recent efforts have extended the upper temperature limit of the DIC technique by the use of optical bandpass filters and narrow band lighting, which reduces the influence of light radiated by the specimen at high temperatures [1][2][3][4][5][6]. Grant et al demonstrated this approach for hightemperature DIC by using blue light along with blue range bandpass filters to measure the coefficient of thermal expansion of RR1000 (a nickel-based alloy) at temperatures up to 1000°C with two-dimensional (2D)-DIC [1].…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar method, Novak and Zok demonstrated the blue-filtering technique on a C/SiC composite at temperatures up to 1500°C [2]. Later, Chen et al and Pan et al applied the blue-filtering technique to stereo-DIC -in which two cameras are used to make three-dimensional (3D) measurements -at temperatures up to 1100 and 1200°C, respectively [3,4]. Most recently, Berke and Lambros showed that the temperature range can be extended even further by using ultraviolet lighting and optics, which operate at an even shorter wavelength than blue light [6].…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, Post and Wood [1] extended the moiré interferometry to measure thermal strains for both steady-state and transient problems. Lyons et al [2] proposed a high-temperature deformation measuring method using digital image correlation (DIC) in 1996, which led to a great development for the DIC technique [3][4][5][6][7][8][9][10][11]. Another method, known as electronic speckle pattern interferometry, was proposed by Dudescu et al [12] in 2006 to measure the thermal deformation of carbon fiber composites and computed the coefficient of thermal expansion (CTE).…”
Section: Introductionmentioning
confidence: 99%
“…To address the first challenge, some authors have used a number of commercial paints and coatings which can withstand high temperatures, including refractory coatings which are rated up to 1760 • C, 3 and cobalt oxide powder which remains black up to its melting temperature of 1900 • C. 4 Alternatively, pre-oxidizing the specimen surface by a limited excursion to a slightly higher temperature can also be used. 5,6 To address the second point, it is common to use an air knife to mix the air in the line of sight of the cameras, thereby reducing the apparent distortion caused by heat haze.…”
Section: Introductionmentioning
confidence: 99%